The Mosque as a Pillar of Social Protection: An Analysis of Zakat Management at Al-Ikhwan Mosque in Empowering the Muslim Community Economy in Sungai Rumbai - Sarori, Yohan; Noer, Melinda; Mahdi, Mahdi (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to analyze the zakat management of the Zakat Management Organization (OPZ) of Al-Ikhwan Mosque in empowering the community’s economy in Nagari Sungai Rumbai and Sungai Rumbai Timur, as well as its alignment with Social Safety Net (JPS) indicators for sustainable economic development. This qualitative research used a case study approach with units of analysis consisting of OPZ administrators, muzakki, and asnaf. The results show that the distribution of consumptive and productive zakat by Al-Ikhwan Mosque’s OPZ has contributed positively to the welfare of mustahik, especially through business capital assistance and systematic zakat distribution. However, program effectiveness still faces obstacles in business assistance, skills training, and long-term impact evaluation. Governance based on the IC COSO framework is adequate in internal control and reporting aspects but needs strengthening in risk assessment and two-way communication. This study produces an Integrated Zakat Management Model based on governance and social protection, which is expected to serve as a reference for other OPZs in developing zakat functions as instruments for community economic empowerment.Keywords: zakat, social safety net, mosque, economic empowerment, governance